Evaluation of socio-demographic characteristics of people was determined to use synthetic cannabinoids in Malatya and its surrounding cities / districts and LC-MS/MS analysis method - Oruc, Mucahit; Petekkaya, Semih; Soylu, Ozcan; Sezer Oner, Bedirhan; Celbis, Osman; Hakan Dinc, Ahmet (Annals of Medical Research, 2021)
Aim: Synthetic cannabinoids (SC) were initially developed in 1960s to target the cannabinoid receptors in medical therapy. However, in recent years, the developed SC derivatives by processing the plant-based material have been sold on websites under the name of natural drugs.The city of Malatya is located at the eastern part of Turkey and has an important location for the transfer and marketing of narcotic substances. In our study, presentation of the socio-demographic characteristics of the cases, the SC was determined in whose blood samples in the analyses, living in Malatya and the surrounding cities-districts were aimed.Materials and Methods: In the scope of study, 275 cases whose blood samples was sent to the Chemistry Department in Forensic Medicine Institute at Malatya Group Presidency in 2016 and were detected as SC-positive by the chemical analysis were investigated.Results: Out of 275 cases, 97.8% were male, 2.2% were female. Median age was 24, 66.5% (n=180) of them were primary school, 18% (n=51) were high school graduate and 0.7% (n=2) were university graduate. The educational status of 27 cases could not be obtained.Conclusion: SC derivatives are marketed with slogan of “the natural ones are harmless”, and their use among the young people is rapidly becoming widespread. In our study, it was determined that the SC users are in the young age group and have low educational status. In order to decrease the number of users, awareness meetings regarding the harmful effects of SC must be organized in the educational institutions.
Keywords: LC-MS/MS; MAM-2201; natural drugs; socio-demographic characteristics; synthetic cannabinoids; THC